Northwest History. Alaska. Dogs, Dog Races & Mushers. (1936)
Pretty Dog Musher May Have Death Along Trail Of Arctic Waste. Pretty Dog Musher May Have Met Death Along Trail of Arctic Waste FAIRBANKS, Alaska, Feb. 27.—(/P)—Fears that diminutive Mary Joyce, 27-year-old dog musher, may have met disaster somewhere along her wilderness trail, were felt here tonight as she was reported five days overdue at Tanana Crossing, a telegraphic communication station 150 miles southeast of here. She has not been reported since she mushed out of Burwash Landing, Yukon Territory, February 9. The comely Taku lodge mistress from Southeastern Alaska, left Burwash with her five dogs and a lone Indian guide named Jimmy Allen. The temperature at that time was 48 degrees below zero. Miss Joyce left Fairbanks December 22 for Fairbanks, 1,000 miles due north. She said she was making the dog-sled journey "just for the experience."